Development of financial innovation and economic growth: An approach using the autoregressive method with staged lags - Blanche, Ngo Yonga Debora; Fidoline, Ngo Nonga (Asian Journal of Empirical Research, 2025)
The objective of this article is to evaluate the effect of the development of financial innovation on economic growth in the CEMAC sub-region during the period 2000-2020. To achieve this objective, the study employed the autoregressive method with staggered lags in a dynamic panel, which is robust to autocorrelation, heteroskedasticity, and potential endogeneity issues. The estimation results revealed that financial innovation has a positive and significant effect on economic growth in the CEMAC zone. Moreover, the analysis of the nonlinear relationship indicates that there is a threshold of 43.15%, beyond which further expansion of financial innovation has a negative and significant impact on economic growth. This suggests a relationship resembling an inverted U-shaped curve between financial innovation and economic growth. Consequently, public authorities within the Economic and Monetary Community of Central Africa (CEMAC) should increase investments in financial infrastructure, such as expanding the number of banking agencies in countries like Gabon and Cameroon, to enhance proximity between ATM services and the population. They should also facilitate access to credit from financial institutions to encourage economic operators to invest in remote areas, thereby increasing access to financial services for impoverished populations. Finally, CEMAC leaders should consider policies that promote the use of mobile money for fund transfers and the expansion of ATM services across member countries, fostering greater financial inclusion and economic development.